Synthetic pyrethroides multiresidue in grapes from southern India - Mahdavian, Seyed Esmaeil; Somashekar, RK (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Pyrethroid is a mixture of pyrethrum I and pyrethrum II, extracted from the plant Chrysanthemum and is used for ultra low volume applications. Pyrethroids may have a range of toxic effects on humans and as a result, careful control of Maximum Residue Limits (MRL) in foodstuff is warranted. Twenty two samples of grapes were procured from Bangalore City Markets in 2007 with the objective of determining the contamination of _-cypermethrin and fenvalerate residues. The samples were extracted by Multiresidue Method and determined by Gas chromatography using ECD (Electron Capture Detector). Average recoveries ranged from 73.5 to 83.5%. The results showed that all the samples were contaminated with pesticides and urban consumers are at a risk of purchasing fresh fruits because of higher levels of residues, beyond the MRL as defined by the FAO/WHO, and grapes committee. The screening also showed higher concentration of cypermethrin in comparison to fenvalerate residue. Key Words: Cypermethrin; Fenvalerate; Grapes; GC/ECD; Bangalore DOI: 10.3126/kuset.v6i2.4018 Kathmandu University Journal of Science, Engineering and Technology Vol.6. No II, November, 2010, pp.104-110